Psychobiological integration during exercise - Balague Serre, N.; Hristovski, R.; Vainoras, A.; Vazquez, P.; Aragones, D. (Complex systems in Sport, 2014)
As has been shown in different experiments, the psychobiological integration is highly likely to be nonlinear, soft-assembled and metastable. In this context, exercise-induced effects and control may be explained through the 'selforganization under constraints' paradigm. This generic mechanism would enable biological systems, through their immense behavioural flexibility and constant striving, to adapt to task and environmental demands. The experimental results suggest that a viable way of investigating psychobiological adaptation during exercise would be to study collective variables, which are products of the cooperative, coordinated interactions among component processes. As has been shown, these potential collective variables may be observed at different levels of the human psychobiological continuum. Thus, it would be especially important to study the ways in which these coordinated dynamics are reconfigured on different time scales and also to carry out more elaborate studies of key control parameters, i.e. configurations of constraints that act upon the stability properties of coordinated states. In this regard, the findings described in this chapter present a challenge for future research and might have important implications for cognitive and physical interventions used to improve performance. Dynamical concepts such as stability, metastability and loss of stability may prove to be important in resolving the extant controversies concerning such interventions and could help to identify suitable strategies for improving performance. While intentions may change the peripheral states (e.g. pacing, etc.), the periphery also seems to constrain the intentions and stability properties of the mind. Hence, the idea of circular causality, which captures not only interaction but also interdependence, rather than a simple, linear top-down cause-effect relationship between the mind and peripheral systems, seems more plausible and provides further evidence of nonlinearity.